How Do CEO Tenure and Narcissism Moderate the Impact Of Sustainability Reporting on Firm Value? Evidence in Indonesia - Agustia, Dian; Fardi Kusuma Dewi, Evita (The Indonesian Journal of Accounting Research, 2025)
Abstract: This is to provide empirical evidence on the impact of sustainability reporting on firm value, moderated by CEO tenure and CEO narcissism. The data for this research encompasses all financial and nonfinancial sectors of companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2022. The analysis uses panel data testing to evaluate 3,645 unbalanced observations. The findings reveal that sustainability reporting has a significant positive effect on firm value, supporting legitimacy theory, which posits that companies must maintain their social performance by fulfilling social needs and creating a positive societal perception, enhancing the company's image and value. However, CEO tenure and narcissism do not strengthen the relationship between sustainability reporting and firm value. The implications of these findings are relevant to managerial decision-makers and academic literature, offering insights into the dynamics of corporate governance and sustainability practices.Keywords: CEO tenure, CEO narcissim, sustainability reporting, firm value Abstrak— Penelitian ini bertujuan untuk memberikan bukti empiris mengenai dampak pelaporan keberlanjutan terhadap nilai perusahaan, dengan moderasi masa jabatan CEO dan narsisisme CEO. Data penelitian ini mencakup seluruh sektor keuangan dan non-keuangan perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) dari tahun 2016 hingga 2022. Analisis menggunakan pengujian data panel untuk mengevaluasi 3.645 observasi tidak seimbang. Temuan menunjukkan bahwa pelaporan keberlanjutan memiliki pengaruh positif yang signifikan terhadap nilai perusahaan, mendukung teori legitimasi yang menyatakan bahwa perusahaan harus menjaga kinerja sosial mereka dengan memenuhi kebutuhan sosial dan menciptakan persepsi positif masyarakat, sehingga meningkatkan citra dan nilai perusahaan. Namun, masa jabatan CEO dan narsisisme tidak memperkuat hubungan antara pelaporan keberlanjutan dan nilai perusahaan. Implikasi dari temuan ini relevan bagi pengambil keputusan manajerial dan literatur akademik, memberikan wawasan tentang dinamika tata kelola perusahaan dan praktik keberlanjutan.Kata Kunci: CEO tenure, CEO narcissim, sustainability reporting, firm value